Penerapan Model Advance Organizer untuk Meningkatkan Kemampuan Pemahaman Siswa - Rezkiyana Hikmah (Universitas Indraprasta PGRI Jakarta, 2017)
This research is aimedat examining the improvement in mathematical understanding ability of students learning with an advance organizer model and those learning with a conventional learning model. This quasi-experimental research uses a non-equivalent control group design and purposive sampling technique. The population of this research is SMPN students in Padang, with the sample consisting of 30 students from class VII which is an experimental class and 30 students from class VII which is a control class. The instruments used are pre-test and post-test administered to the students to test their mathematical understanding ability. The data are analyzed applying the average difference test (independent samples t-test and Mann-Whitney U test). The result of the research shows students learning with an advance organizer model have an improvement in mathematical understanding ability better than those learning with a conventional learning model.